2023
DOI: 10.3390/s23135941
|View full text |Cite
|
Sign up to set email alerts
|

CICIoT2023: A Real-Time Dataset and Benchmark for Large-Scale Attacks in IoT Environment

Abstract: Nowadays, the Internet of Things (IoT) concept plays a pivotal role in society and brings new capabilities to different industries. The number of IoT solutions in areas such as transportation and healthcare is increasing and new services are under development. In the last decade, society has experienced a drastic increase in IoT connections. In fact, IoT connections will increase in the next few years across different areas. Conversely, several challenges still need to be faced to enable efficient and secure o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(41 citation statements)
references
References 73 publications
0
41
0
Order By: Relevance
“…The corresponding confusion matrix can be found in Figure 6 As a final assessment of the outcomes derived from the process of evaluation, Table 7 provides a comprehensive analysis of the overall performance of the model proposed by our work as compared to the State-of-the-Art models on the CICIoT2023 dataset. Notwithstanding, the obtained results indicate that our model, when compared to the related-work on the CICIoT2023 dataset, achieves a level of accuracy and TPR that surpasses that of [29], although it falls slightly short in comparison to [39]. Nevertheless, our model still exhibit exceptional performance, particularly in terms of PPV and F-score metrics, surpassing those of the State-of-the-Art in both binary and multi-class classification scenarios.…”
Section: Experimental Analysismentioning
confidence: 68%
See 2 more Smart Citations
“…The corresponding confusion matrix can be found in Figure 6 As a final assessment of the outcomes derived from the process of evaluation, Table 7 provides a comprehensive analysis of the overall performance of the model proposed by our work as compared to the State-of-the-Art models on the CICIoT2023 dataset. Notwithstanding, the obtained results indicate that our model, when compared to the related-work on the CICIoT2023 dataset, achieves a level of accuracy and TPR that surpasses that of [29], although it falls slightly short in comparison to [39]. Nevertheless, our model still exhibit exceptional performance, particularly in terms of PPV and F-score metrics, surpassing those of the State-of-the-Art in both binary and multi-class classification scenarios.…”
Section: Experimental Analysismentioning
confidence: 68%
“…It has been observed that the majority of datasets available are outdated lacking reliability due to the absence of dependable validation and testing [29]. This is primarily due to having limited volume of data and deficient diversity in terms of traffic.…”
Section: Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Through our focus on this rich dataset, combined with innovative preprocessing techniques, we contributed to advancing intrusion detection systems by achieving higher F1 scores and lower training and prediction times. [27].…”
Section: Authorsmentioning
confidence: 99%
“…As stated in the related works section, the dataset used in this study was the CICIoT2023 dataset, which was made publicly available by Neto et al [27].…”
Section: Data Preprocessingmentioning
confidence: 99%